DINAMISASI TRADISI KEAGAMAAN KAMPUNG JAWA TONDANO DI ERA MODERN - Otta, Yusno Abdullah (LP2M IAIN Mataram, 2010)
This paper discusses the form and diversity of religious traditions among the Javanese community in Tondano, North Sulawesi. For the Javanese in that area, religious traditions serve as a distinct symbol that culturally and ideologically distinguish them from others. Besides, their religious traditions constitute the most effective medium to preserve their identity as Muslim and Javanese. Nevertheless, their distinctive traditions have hardly become troublesome that deters them from making harmonious relations with their surrounding communities who hold different ideology and culture. This study reveals that the changing time and modernity do not significantly impede them from practicing their religious traditions. The community of Kampung Jawa in Tondano, Minahasa, has consistently maintained the religious traditions that they inherited from their forebears.